The creation of new states through interim agreements: Ambiguous compromises, intra-communal divisions, and contested identities. Issue 5 (November 2020) - Caspersen, Nina
For some separatist movements, interim agreements offer a possible route to recognized statehood. However, such agreements require these movements to compromise on their demand for immediate independence and risk the preservation of the joint state. How is this reconciled with their claim to self-determination and how is it received by the community they claim to represent? This article examines four post-Cold War cases where an interim agreement has been accepted (New Caledonia, Bougainville, Montenegro and South Sudan). It finds that interim agreements are more easily accepted when the community is significantly divided on the issue of independence and when an inclusive and flexible construction of the community predominates. Somewhat paradoxically, this suggests that new states are more likely to emerge in cases without a determined, cohesive, ethnically defined demand for independence.